Léon Blum before his judges at the Suppreme Court of Riom, March 11th and 12th, 1942 - Attlee, Clement; Gouin, Félix; Blum, Léon (London : Labour Party, 1943)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Blum, Léon; Wereldoorlog 2; Frankrijk